Routledge handbook of regionalism & federalism - Kincaid, John.; Loughlin, John.; Swenden, Wilfried ([S.l.] : Routledge, 2013)
Almost all states are either federal or regionalized in some sense. It is difficult to find a state that is entirely unitary and the Routledge Handbook of Regionalism and Federalism necessarily takes in almost the entire world. Both federalism and regionalism have been subjects of a vast academic literature mainly from political science but sometimes also from history, economics, and geography. This cutting edge examination seeks to evaluate the two types of state organization from the perspective of political science producing a work that is analytical rather than simply descriptive. The Handbook presents some of the latest theoretical reflections on regionalism and federalism and then moves on to discuss cases of both regionalism and federalism in key countries chosen from the world$1 (Bs macro-regions. Assembling this wide range of case studies allows the book to present a general picture of current trends in territorial governance. The final chapters then examine failed federations such as Czechoslovakia and examples of transnational regionalism - the EU, NAFTA and the African Union. Covering evolving forms of federalism and regionalism in all parts of the world and featuring a comprehensive range of case studies by leading international scholars this work will be an essential reference source for all students and scholars of international politics, comparative politics and international relations.s
Keywords: Federal government; Regionalism